2022
DOI: 10.1016/j.ebiom.2021.103795
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complex interplay between genes, environment, and climate in ALS

Abstract: Various genetic and environmental risk factors have been implicated in the pathogenesis of amyotrophic lateral sclerosis (ALS). Despite this, the cause of most ALS cases remains obscure. In this review, we describe the current evidence implicating genetic and environmental factors in motor neuron degeneration. While the risk exerted by many environmental factors may appear small, their effect could be magnified by the presence of a genetic predisposition. We postulate that gene-environment interactions account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 120 publications
(187 reference statements)
1
30
0
Order By: Relevance
“…Although both population and hospital survey studies showed an increased risk of farmers and rural residents, our study did not show a statistically significant association between farmers, rural residents, and the development of ALS because of the limited sample. The multiple coexisting conditions seen in farmers and rural residents may confer greater susceptibility to ALS, such as associated environments, education and physical power, and so on, which is, in part, supported by the higher prevalence seen in our study than in previous studies (Ludolph et al, 2012 ; Zarei et al, 2015 ; Vasta et al, 2022 ). The profession in agriculture was risk work for the development of ALS in the Chinese mainland.…”
Section: Discussionsupporting
confidence: 84%
“…Although both population and hospital survey studies showed an increased risk of farmers and rural residents, our study did not show a statistically significant association between farmers, rural residents, and the development of ALS because of the limited sample. The multiple coexisting conditions seen in farmers and rural residents may confer greater susceptibility to ALS, such as associated environments, education and physical power, and so on, which is, in part, supported by the higher prevalence seen in our study than in previous studies (Ludolph et al, 2012 ; Zarei et al, 2015 ; Vasta et al, 2022 ). The profession in agriculture was risk work for the development of ALS in the Chinese mainland.…”
Section: Discussionsupporting
confidence: 84%
“…18,19 However, identifying the mechanisms underlying the wide phenotypic heterogeneity of ALS, which hinders the discovery of effective therapies, 2 remains one of the significant unmet goals of ALS research. ALS heterogeneity is likely due to an interplay between genetics, age, gender, 1,20 and All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
“…The precise causes of PD are largely unknown, and several etiologic factors, including aging, genetic and environmental factors, and gender ( Ascherio and Schwarzschild, 2016 ), have been shown to increase the risk of PD development. One risk factor, or a combination of two or more factors, can distinctly contribute to PD pathogenesis ( Pang et al, 2019 ; Vasta et al, 2021 ). Among these factors, aging is considered as the number one risk factor for PD development and progression ( Hindle, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several gene mutations have been shown to be the major cause of early onset PD (diagnosed in individuals younger than 45 years old) ( Schrag and Schott, 2006 ), implying a superimposed effect of genetic factors on age-related PD pathogenesis. It is notable that PD is induced by a combination of aging with environmental and/or genetic factors ( Pang et al, 2019 ; Vasta et al, 2021 ). Environmental factors include exposure to toxins and chemicals, which are associated with an increased risk of PD ( Chen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%